Hepatitis B vaccination with HepB-CpG in people living with HIV: a narrative review - Kelvin McKoy; Stephanie Campbell; Patricia Novy; Robert S. Janssen (Expert Review of Vaccines)
Introduction To eliminate hepatitis B virus (HBV) globally, a key focus is preventing new infections among high-risk individuals, including those with HIV. The widespread incidence of HBV and HIV leads to a high rate of coinfection. HIV compromises the immune system, significantly increasing the risk of chronic HBV infection, cirrhosis, liver cancer, and death from liver-related disease among coinfected individuals.Areas covered This review explores recent research on the two-dose HepB-CpG (HEPLISAV-B) vaccine, which is a potential solution to the challenge of suboptimal immune responses to three-dose HBV vaccines (HepB-alum) in people living with HIV (PLWH). We compare the immunogenicity and safety of HepB-CpG in both vaccine-naive and previously vaccinated nonresponding PLWH populations.Expert opinion Compared with three-dose HepB-alum vaccines, HepB-CpG offers a more convenient two-dose schedule, which could increase series completion rates. HepB-CpG might be more immunogenic in vaccine-naive and vaccine-experienced PLWH. Both attributes make HepB-CpG a possible future standard of care for adult HBV vaccination in PLWH.